Association between stressful life events and psychotic experiences in adolescence: Evidence for gene–environment correlations. (2nd January 2018) - Shakoor, Sania; Zavos, Helena M. S.; Haworth, Claire M. A.; McGuire, Phillip; Cardno, Alastair G.; Freeman, Daniel; Ronald, Angelica
Abstract : Background: Stressful life events (SLEs) are associated with psychotic experiences. SLEs might act as an environmental risk factor, but may also share a genetic propensity with psychotic experiences. Aims: To estimate the extent to which genetic and environmental factors influence the relationship between SLEs and psychotic experiences. Method: Self- and parent reports from a community-based twin sample (4830 16-year-old pairs) were analysed using structural equation model fitting. Results: SLEs correlated with positive psychotic experiences ( r = 0.12–0.14, all P <0.001). Modest heritability was shown for psychotic experiences (25–57%) and dependent SLEs (32%). Genetic influences explained the majority of the modest covariation between dependent SLEs and paranoia and cognitive disorganisation (bivariate heritabilities 74–86%). The relationship between SLEs and hallucinations and grandiosity was explained by both genetic and common environmental effects. Conclusions: Further to dependent SLEs being an environmental risk factor, individuals may have an underlying genetic propensity increasing their risk of dependent SLEs and positive psychotic experiences.